EFFECT OF DECOCTA IN BITTER MELON FRUIT (MomordicacharantiaL.) FOR DECREASE BLOOD GLUCOSE LEVELS - Sayoeti, Azatu Zahirah (Majority, 2015)
Abstract Diabetes mellitus is a metabolic disease that causes multifactorial, resulting in hyperglycemia and hyperinsulinemia. The disease is characterized by the presence of insulin resistance in muscle tissue, fat and liver. Bitter melon with charantin content that can stimulate Beta cells of Langerhans islands, polypeptide-p which is a polypeptide similar to insulin, and glycosides which can increase pressure on the smooth muscle of the intestinal wall. The study aims to prove the efficacy of bitter pare fruit that can lower blood glucose levels. Keywords: bitter melon fruit, Charantin, Diabetes mellitus Abstrak Diabetes melitus merupakan penyakit metabolik yang penyebabnya multifaktorial sehingga terjadi hiperglikemia dan hiperinsulinemia. Penyakit ini ditandai dengan adanya resistensi insulin di jaringan otot, lemak dan hati. Buah pare dengan kandungan charantin yang dapat menstimulasi (merangsang) sel-sel Beta pulau langerhans, polipeptida-p yang merupakan polipeptida mirip insulin, dan glikosida yang mampu meningkatkan tekanan otot polos pada dinding usus. Penelitian bertujuan membuktikan khasiat dari buah pare yang dapat menurunkan kadar glukosa darah. Kata Kunci: buah pare, Charantin, Diabetes melitus